A revision of the gobiid fish genus Trypauchen (Gobiidae: Amblyopinae) - Murdy, Edward O. (Zootaxa, 2006)
The Indo-West Pacific gobiid genus Trypauchen is diagnosed and revised. Trypauchen is unique within the Amblyopinae in having the following combination of characters: 1) typically four, rarely three, anal-fin pterygiophores anterior to the first hemal spine; 2) pelvic fins small, united, and funnel-shaped with a well-developed interradial membrane; and 3) abdomen scaled. Trypauchen comprises two species: T. pelaeos n. sp., known from Myanmar, Malaysia, Thailand, Vietnam, and China; and T. vagina, distributed from Kuwait, along the coasts of India, ranging eastward to the Philippines, Taiwan, and China. A key to species is provided. Figures and descriptions of each species are also given. Putative relationships of the genus are discussed.